Analisis Customer Satisfaction dan Brand Trust terhadap Customer Retention - Gladis Sarah Aurelia; Asep M. Ramdan; Acep Samsudin (Journal of Management and Bussines (JOMB), 2019)
The aim this research is to know the influence of customer satisfaction and brand trust toward customer retention. The method of this research is using kind of samples including random samples and questionnaires to 101 consumers. The analytical technique, in here is multiple linear analysis technique, and for the hypotesis testing, we use statistic test partially (testing t) and simultaneous test (testing f). The reseacrh result for testing t indicates that both customer satisfaction (X1) and brand trust (X2) have significant influence towards customer retention (Y). According to probability value of sig. 0,000 < 0,05 means that both satisfaction (X1) and brand trust (X2) have significant influence towards customer retention (Y). Keywords : Customer Satisfaction, Brand Trust, Customer Retention